Pemberdayaan Kelompok Tani Unggas Jaya Melalui Teknologi Monitoring Gas Amonia Dan Suhu Kandang Otomatis Berbasis IoT - Risald, Risald; Baso, Budiman; Ullu, Hevi Herlina; Lisnahan, Charles Venirius (STMIK Royal, 2024)
The Poultry Jaya farmer group is in the city of Kefamenanu, the native chicken farming system of the Jaya Poultry Group is still conventional. One of the main problems faced by this group is the lack of monitoring and controlling the temperature of the cage as well as monitoring the ammonia gas produced by chicken droppings. Temperature and ammonia gas levels have a major impact on chicken growth and health. To overcome this problem, it is necessary to implement Internet of Things (IoT) technology integrated with Android applications. This technology allows automatic and periodic monitoring of cage temperature and ammonia gas levels. Farmers can access information via the Android app and take necessary action if significant changes occur. This community service aims to build tools and systems for automatic temperature control and IoT-based ammonia levels integrated with Android, as well as introducing technology and providing training and assistance to the Unggas Jaya farmer group regarding IoT technology in chicken coop management. With the existence of IoT technology, it is hoped that the behavior patterns of farmers will change to become more modern and efficient. This technology can help improve poultry farming performance, reduce risks, and provide convenience in cage management so that it will bring positive changes to the productivity and welfare of farmers. Keywords: Poultry Jaya farmer group; chicken coop; Internet of Things (IoT)